Type 2 Diabetes Increases Risk of Unfavorable Survival Outcome for Postoperative Ischemic Stroke in Patients Who Underwent Non-cardiac Surgery: A Retrospective Cohort Study - Zhang, Faqiang; Ma, Yulong; Yu, Yao; Sun, Miao; Li, Hao; Lou, Jingsheng; Cao, Jiangbei; Liu, Yanhong; Niu, Mu; Wang, Long; Mi, Weidong (Frontiers in Aging Neuroscience, 2022)
Objective: Diabetes mellitus (DM) has been critically associated with unfavorable outcomes in the general population. We aimed to investigate the association between type 2 DM and long-term survival outcomes for postoperative ischemic stroke in patients who underwent non-cardiac surgery. Research Design and Methods: This was a retrospective cohort study of patients with non-cardiac surgery who had suffered from postoperative ischemic stroke between January 2008 and August 2019. Diabetic individuals were included in postoperative ischemic stroke patients with the DM group. The outcome of interest was long-term overall survival (OS). We conducted propensity score matching (PSM) and inverse probability treatment weighting (IPTW) to adjust for baseline characteristic differences between groups. Multivariate Cox regression analysis with stepwise selection was used to calculate the adjusted hazard ratio (HR) of OS and type 2 DM. Results: During a median follow-up of 46.2 month [interquartile range (IQR), 21.1, 84.2], 200 of 408 patients (49.0%) died. The OS rates at 3, 5, and 10 years were significantly lower for postoperative ischemic stroke patients with DM than those without DM (3 years OS: 52.2 vs. 69.5%, p < 0.001; 5 years OS: 41.6 vs. 62.4%, p < 0.001; 10 years OS: 37.2 vs. 56.6%, p < 0.001). All covariates were between-group balanced after using PSM or IPTW. The postoperative ischemic stroke patients with type 2 DM had a shortened OS in primary analysis (HR: 1.947; 95% CI: 1.397–2.713; p < 0.001), PSM analysis (HR: 2.190; 95% CI: 1.354–3.540; p = 0.001), and IPTW analysis (HR: 2.551; 95% CI: 1.769–3.679; p < 0.001). Conclusion: Type 2 DM was associated with an unfavorable survival outcome for postoperative ischemic stroke in patients who underwent non-cardiac surgery. When postoperative ischemic stroke co-occurred with type 2 DM, the potential synergies would have multiplicative mortality risk. Further research to assess the adverse effects of type 2 DM on long-term survival may be warranted.